Penerapan Lean Manufacturing Untuk Meminimasi Pemborosan Pada Bahan Baku Kerangka Sofa di UD. Sofa Bandar Tinggi - Damanik, Ricky Prayuda; Siregar, Ninny Asnidar; Polewangi, Yudi Daeng (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2023)
UD. Sofa Bandar Tinggi is an UMKM in the manufacturing sector with sofa production. In producing sofas in the production process there is still waste. The wastage that occurred in the last year was as much as 17 sets of overproduction, 17 sets of unnecessary inventory, 22 sets of defects and 45 minutes of waiting time. Therefore, it is necessary to identify waste and analyze the causes of this waste to increase productivity by implementing lean manufacturing in the sofa production process using value stream mapping to determine product flow and information flow that support other activities and also to eliminate waste and find the causes of this waste by fishbone diagrams. Based on the current value stream mapping results, the lead time is 109.63 minutes, the value added is 94.21 minutes. After the process activity mapping was carried out, the current stream mapping future state results showed that the lead time decreased to 98.26 minutes. And also the translation of a problem from the fishbone diagram, namely the man factor (lack of discipline, low skill of workers), measurement (repeated wood cutting), method (uneven wood pieces), material (inappropriate wood thickness). The recommendations for improvement to minimize waste are in the form of Standard Operation Procedures and implementing 5S.